Urban underclass labourers - the life of delivery workers in South India - Das, Sikha and Rajeesh, C .S. (Economic and Political Weekly)
Delivery workers who constantly battle job insecurity and poor pay scales are excluded urban underclass workers. The squeezed labour policies of popular corporate food-ordering apps in India have been a catalyst for delivery workers to break their silence and form a unified working class consciousness. The online platform workers face exploitation and inequality as they are defined by platforms as delivery partners or independent contractors, which keep them outside the gambit of any social security schemes.- Reproduced